The concept of steadfast (Al-IcTisam) to the Qur’an and the Sunnah: the foundation of Islamic teaching for humanizing mankind - Azwira Abdul Aziz,; Aminudin Basir@Ahmad,; Azizi Umar,; Syaidatun Nazirah Abu Zahrin,; Hazman Hassan, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The Qur’an as well as the Sunnah are revelation sources for all explanation and orientation of Islamic knowledge. There are very sound and clear textual evidences with commits Muslims to perform al-Ictisam of both sources. Al-Ictisam or holding fast to the Qur’an and the Sunnah, is the Islamic principle expressed by the revelation through analogical style of language. To evade misconceptions and confusions, the analogy necessitates further explanation. Hence this article intends to elucidate the concept of performing al-Ictisam to the Qur’an and the Sunnah according to the authoritative methodology of Islamic knowledge. The concept of al-Ictisam to the Qur’an and the Sunnah should be observed from the aspects of faith, study, understanding, practice, appreciation as well as Islamic call (da’wah).